Testing connections between exo-atmospheres and their host stars: GEMINI-N/GMOS ground-based transmission spectrum of Qatar-1b - Essen, C. von (2017)
Till date, only a handful exo-atmospheres have been well characterized, mostly by means of the transit method. Some classic examples are HD 209458b, HD 189733b, GJ-436b, and GJ-1214b. Data show exoplanet atmospheres to be diverse. However, this is based on a small number of cases. Here we focus our study on the exo-atmosphere of Qatar-1b, an exoplanet that looks much like HD 189733b regarding its host star's activity level, their surface gravity, scale height, equilibrium temperature and transit parameters. Thus, our motivation relied on carrying out a comparative study of their atmospheres, and assess if these are regulated by their environment. In this work we present one primary transit of Qatar-1b obtained during September, 2014, using the 8.1 m GEMINI North telescope. The observations were performed using the GMOS-N instrument in multi-object spectroscopic mode. We collected fluxes of Qatar-1 and six more reference stars, covering the wavelength range between 460 and 746 nm. The achieved photometric precision of 0.18 parts-per-thousand in the white light curve, at a cadence of 165 s, makes this one of the most precise datasets obtained from the ground. We created 12 chromatic transit light curves that we computed by integrating fluxes in wavelength bins of different sizes, ranging between 3.5 and 20 nm. Although the data are of excellent quality, the wavelength coverage and the precision of the transmission spectrum are not sufficient to neither rule out or to favor classic atmospheric models. Nonetheless, simple statistical analysis favors the clear atmosphere scenario. A larger wavelength coverage or space-based data is required to characterize the constituents of Qatar-1b's atmosphere and to compare it to the well known HD 189733b. On top of the similarities of the orbital and physical parameters of both exoplanets, from a long Hα photometric follow-up of Qatar-1, presented in this work, we find Qatar-1 to be as active as HD 189733.